Altorientalische Altertümer in Museen und Privatsammlungen - Weidner, Ernst
London, British Museum (Abb. 6-17a) – Birmingham (Museum and Gallery) – Newcastle upon Tyne – New York (Metropolitan Museum of Art) – Boston (Museum of Fine Arts) – Philadelphia (University Museum).